Hubungan pengetahuan gizi, tingkat kecukupan zat gizi, dan aktivitas fisik dengan status gizi pada guru SMP - Soraya, Dinah; Sukandar, Dadang; Sinaga, Tiurma (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: The quality of human resources is a major factor necessary for the successful implementation of national development. Teachers have a very important role in the development of human resources in the field of education. Empirical evidence indicates quality of human resources determined from good nutritional status, and this is determined by nutritional knowledge, the amount of food intake consumed and the physical activity of a person.Objective: The aim of this study was to analyze the relationship between nutritional knowledge, nutritional adequacy level, and physical activity with nutritional status ofÂ teacher in SMPN 1 Dramaga Bogor. Methods: The research design used was cross sectional with total of 35 subjects. The data collected consist of data individual and family characteristic, nutritional status, food consumption, physical activity, fitness index, sporting habit, nutritional knowledge and general description of the school. The method of this research is most of the subjects (74.3%) is women with average age classified into middle adult to last adult. Result: Most of the subjects (68.6%) was government employeeÂ with average working time was 6 to 8 hours. Most of the subjects have nutritional status obesity chategorized (51.4%). Energy consumption level was classified as medium deficits, protein was low deficits, fats excessive and carbohydrates sufficient. The average level of physical activity on the weekend clasified low, whereas on the weekday classified medium. Most subjects have very low levels of fitness (71.4%) and their knowledge of nutrition was sufficient (74.3%). Conclusion: There was a significant possitive correlation between work time (p=0.023, r=0.384) and sporting habit with BMI (p=0.011, r=0.504).